2014
DOI: 10.3389/fmicb.2014.00283
|View full text |Cite
|
Sign up to set email alerts
|

Building the crops of tomorrow: advantages of symbiont-based approaches to improving abiotic stress tolerance

Abstract: The exponential growth in world population is feeding a steadily increasing global need for arable farmland, a resource that is already in high demand. This trend has led to increased farming on subprime arid and semi-arid lands, where limited availability of water and a host of environmental stresses often severely reduce crop productivity. The conventional approach to mitigating the abiotic stresses associated with arid climes is to breed for stress-tolerant cultivars, a time and labor intensive venture that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(102 citation statements)
references
References 66 publications
1
99
1
1
Order By: Relevance
“…Several free-living PGPR strains can facilitate plants' acquisition of nutrients from their surroundings, and help them resist soil-borne pathogens [1,2]. Ample evidence has indicated that the microbial release of VOCs triggers plant growth without physical contact with the roots [9][10][11]. The shift of soil microbes to belowground space is physically constrained by the soil, whereas mVOCs can easily diffuse into the rhizosphere and reach the aboveground tissues of plants [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several free-living PGPR strains can facilitate plants' acquisition of nutrients from their surroundings, and help them resist soil-borne pathogens [1,2]. Ample evidence has indicated that the microbial release of VOCs triggers plant growth without physical contact with the roots [9][10][11]. The shift of soil microbes to belowground space is physically constrained by the soil, whereas mVOCs can easily diffuse into the rhizosphere and reach the aboveground tissues of plants [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiomes of animals and plants are often dominated by eubacteria, but fungi, protozoa, archaea, and viruses also can play important roles in these communities [1][2][3][4][5]. Microbiomes are not passive players [6,7]; rather, microbes can alter host development, physiology, and systemic defenses [2,8,9], enable toxin production and disease resistance [10,11], increase host tolerance to stress and drought [12][13][14], modulate niche breadth [15], and change fitness outcomes in host interactions with competitors, predators, and pathogens [6]. Because microbiomes can encompass a hundred-fold more genes than host genomes [16], and because this 'hologenome' of a hostmicrobiome association can vary over space and time [17,18], microbiomes can function as a phenotypically plastic buffer between the host-genotype's effects and the environmental effects that interact to shape host phenotypes.…”
Section: Microbiome Engineeringmentioning
confidence: 99%
“…While inoculation with microbes can confer traits such as resistance to nematode pests (Flor-Peregrin et al 2014) and environmental stress (Coleman-Derr et al 2014), they often do not survive when introduced into a new environment and so are unable to control pathogens effectively (Mazzola 2004). For example, UC researchers found that the microbial communities of soil where commercial inoculants were applied were similar to uninoculated soils, and that inoculants had no effect on tree vigor (Drenovsky et al 2005).…”
Section: Inoculationmentioning
confidence: 99%